PENYELESAIAN KONFLIK PEMUTUSAN HUBUNGAN KERJA: Resolution Of Employment Termination Disputes Without Following The Mechanism In Accordance With The Legislation - Syahdan Sabillah; Yogo Pamungkas (Reformasi Hukum Trisakti, 2024)
Settlement of industrial relations disputes between companies and workers based on regulations on the settlement of industrial relations disputes must go through bipartite negotiations, mediation, or conciliation. The problem in this study is whether the settlement of the layoff conflict between Zainal Hakim and PT. Sukses Wijaya Adimakmur is in accordance with the Law on the Settlement of Industrial Relations Disputes and whether the decision of the Banjarmasin Industrial Relations Court judge in deciding the conflict between Zainal Hakim and PT. Sukses Wijaya Adimakmur is in accordance with Ministerial Regulation Number 35 of 2021. This writing uses a descriptive normative research method, data sources come from secondary data and are analyzed qualitatively, and conclusions are drawn using deductive methods. The result and conclusion are the procedure for resolving the layoff conflict carried out by the parties is not in accordance with regulations because it did not go through the initial stages of bipartite, mediation, or conciliation, so in the Banjarmasin District Court Decision Number 25/Pdt. Sus-PHI/2022/PN.Bjm there are formal defects in its settlement. In the judge's decision regarding the Demotion and Termination of Employment, it is legally valid, but in terms of the provision of severance pay, it is not accordance with statutory regulations.